The epidemiology of oral cancer during the COVID-19 pandemic in Northern Italy: Incidence, survival, prevalence - Mangone, Lucia; Mancuso, Pamela; Bisceglia, Isabella; Setti, Giacomo; Malaguti, Giuliano; Giorgi Rossi, Paolo (Frontiers in Oral Health, 2022)
Despite novel treatment approaches, oral cancer survival has not improved significantly and the disease often presents a disabling path for patients. The aim of this work was to describe the epidemiological data of oral cancers in a province of northern Italy. Incident cases in the period 1996-2020 and EU population standardized rates were reported for Oral Cavity cancer (OC) and OroPharyngeal cancer (OP). Annual percent changes (APC) were estimated with joint point analysis. The 5-year survival was calculated in three different periods: 1996-2000, 2001-2010 and 2011-2015. From 1996 to 2020, 771 cases of oral cancers (442 OC and 329 OP) were recorded with the age-standardized incidence rate 7.28 (10.74 in males and 3.97 in females): 3.82 for OC and 3.47 for OP. In males there is a significant increase in the incidence of OP up to 2017 (APC 11; 95% CI 4.9-17.5), which then decreases; in females the rates are constant. In 2020 (the era of Covid-19), we did not see a decline in incidence compared to 2019. The 5-year survival (for cases diagnosed in 2011-2015) was 55.6%, 56.5% and 56% for OC, OP and OC + OP, respectively; it was somewhat higher in females and was undergoing some changes over the course of years. The number of prevalent cases as of January 1, 2021 is 314 (175 OC, 139 OP). The study showed a decline in cancers in men, particularly for OP; survival shows improvement in the long-term examined; Covid-19 had no negative impact on 2020 diagnoses.